Nutritional and Therapeutic Management of Ruminal Dysfunction in Dairy Cows Affected with Trypanosomosis - Mohanta, Ranjan K; Mahesh, M.S.; Behera, Suvendu K.; Behera, Bijay K.; Sahoo, Tusar R.; Sethy, Sujata; Sarangi, Dillip R. (Indian Journal of Animal Nutrition, 2022)
It is well established that trypanosomosis as well as trypanocidal drugs elicit their adverse effects on rumen microflora and fauna, leading to severe depression of appetite in ruminants. Despite the fact, a very less attention has been paid to restore rumen functions using nutritional and therapeutic interventions during its treatment under field conditions. This report considered two dairy cows affected with Trypanosoma evansi that were treated by trypanocidal drug and exhibiting anorexia for more than five days. The supportive therapy included supplementing probiotics plus rumen stabilizing/conditioning agents (i.e., ruminotorics and stomachics), which normalized the appetite by day three post therapy and the cows recovered uneventfully. Thus, the current findings reinforce to consider nutritional interventions to restore ruminal health when treating cows suffering from trypanosomosis under field conditions.